La radiodiffusion sur ondes courtes et l’interprète de conférence - Gile, Daniel (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1991)
AbstractConference interpreting is believed to require maintenance work, both in linguistic terms and in terms of information. International shortwave broadcasting provides a very convenient linguistic and informational resource to the interpreter, as if makes information originating from distant countries and presented orally in several languages available to him at the cost of a radio. Regular and useful listening implies selecting powerful stations, so that sophisticates receivers are not required. Small portable transistor radios with PLL-tuning circuits are well suited to interpreters needs. The paper lists the adavantages of SW broadcasting, explains its use in maintenance and training from both the linguistic and informational points of view. It also gives some practical information on frequencies and receivers and lists sources of further information.